Activity of β-Lactamase Inhibitor Combinations Against Enterobacterales Isolated from Patients with Intra-Abdominal Infection from United States Medical Centres (2019–2023) - Helio S. Sader; John H. Kimbrough; Marisa L. Winkler; Rodrigo E. Mendes; Mariana Castanheira (Antibiotics)
Objective: To evaluate the antimicrobial susceptibility of Enterobacterales isolated from patients with intra-abdominal infections (IAI) in United States (US) medical centres. Methods: A total of 2036 isolates (1/patient) were consecutively collected from patients with IAI in 63 US hospitals in 2019–2023 and susceptibility tested by broth microdilution. Carbapenem-resistant Enterobacterales (CRE) were screened for carbapenemases by whole genome sequencing. Results: The most common Enterobacterales species were E. coli (47.1%), K. pneumoniae (18.7%), and E. cloacae species complex (9.8%). The most active agents were aztreonam-avibactam (MIC50/90, ≤0.03/0.12 mg/L), ceftazidime-avibactam (MIC50/90, 0.12/0.25 mg/L), and meropenem-vaborbactam (MIC50/90, 0.03/0.06 mg/L) with 99.9% susceptibility. A multidrug-resistant (MDR) phenotype (nonsusceptibility to ≥3 classes) was observed in 21.4% of Enterobacterales (n = 436). Piperacillin-tazobactam was active against 87.2% of Enterobacterales overall and 50.2% of MDR isolates, and meropenem was active against 99.2% of Enterobacterales and 96.1% of MDR isolates. Only 51.6% of Enterobacterales were susceptible to ampicillin-sulbactam. An acquired broad-spectrum β-lactamase gene was identified in 207 (10.2%) isolates and included extended-spectrum β-lactamases (ESBL; n = 182), transferable AmpC (n = 24) and carbapenemases (n = 9). Eight isolates produced two β-lactamase classes. Conclusions: Aztreonam-avibactam, ceftazidime-avibactam, and meropenem-vaborbactam exhibited almost complete activity (99.9% susceptibility) against Enterobacterales causing IAI in US hospitals. In contrast, piperacillin-tazobactam exhibited limited activity against these organisms, especially those with a MDR phenotype.